2007
DOI: 10.1577/m05-142.1
|View full text |Cite
|
Sign up to set email alerts
|

Population Dynamics and Angler Exploitation of the Unique Muskellunge Population in Shoepack Lake, Voyageurs National Park, Minnesota

Abstract: A unique population of muskellunge Esox masquinongy inhabits Shoepack Lake in Voyageurs National Park, Minnesota. Little is known about its status, dynamics, and angler exploitation, and there is concern for the long-term viability of this population. We used intensive sampling and mark-recapture methods to quantify abundance, survival, growth, condition, age at maturity and fecundity and angler surveys to quantify angler pressure, catch rates, and exploitation. During our study, heavy rain washed out a dam co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
38
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(39 citation statements)
references
References 19 publications
(20 reference statements)
1
38
0
Order By: Relevance
“…Moreover, Frohnauer et al (2007) and Strand (1986) observed a 4.1% and 0% mortality rate of angled muskellunge from Shoepack Lake in Voyageurs National Park and Leech Lake, Minnesota, respectively. The C&R mortality rates reported in the present study Frohnauer et al (2007) and Strand (1986) are markedly lower than those reported for other freshwater species (see Muoneke and Childress, 1994;Bartholomew and Bohnsack, 2005), but are consistent with mortality rates in specialized fisheries that are often less than 5% and sometimes below 0.1% (Policansky, 2002). Although no mortalities were observed in this study, it should be acknowledged that zero risk of angling mortality is never achievable in a fishery (Arlinghaus et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Frohnauer et al (2007) and Strand (1986) observed a 4.1% and 0% mortality rate of angled muskellunge from Shoepack Lake in Voyageurs National Park and Leech Lake, Minnesota, respectively. The C&R mortality rates reported in the present study Frohnauer et al (2007) and Strand (1986) are markedly lower than those reported for other freshwater species (see Muoneke and Childress, 1994;Bartholomew and Bohnsack, 2005), but are consistent with mortality rates in specialized fisheries that are often less than 5% and sometimes below 0.1% (Policansky, 2002). Although no mortalities were observed in this study, it should be acknowledged that zero risk of angling mortality is never achievable in a fishery (Arlinghaus et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Their estimate, however, was made in a laboratory setting and may have introduced handling and confinement-related stressors resulting in an elevated mortality rate (Pollock and Pine, 2007;Donaldson et al, 2008). Moreover, Frohnauer et al (2007) and Strand (1986) observed a 4.1% and 0% mortality rate of angled muskellunge from Shoepack Lake in Voyageurs National Park and Leech Lake, Minnesota, respectively. The C&R mortality rates reported in the present study Frohnauer et al (2007) and Strand (1986) are markedly lower than those reported for other freshwater species (see Muoneke and Childress, 1994;Bartholomew and Bohnsack, 2005), but are consistent with mortality rates in specialized fisheries that are often less than 5% and sometimes below 0.1% (Policansky, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The apparent inability of the Shoepack strain to attain large sizes (Younk and Strand 1992;Frohnauer et al 2007) was a concern because muskellunge primarily support trophy fisheries (Margenau and AveLallemant 2000;Wingate and Younk 2007). Factors that might affect growth and size structure in muskellunge include prey characteristics (Wahl andStein 1988, 1993), water temperature (Bevelhimer et al 1985;Wahl and Stein 1991;Clapp and Wahl 1996), angling (Margenau and Hanson 1996), and genetics (Margenau and Hanson 1996;Younk and Strand 1992;Clapp and Wahl 1996).…”
mentioning
confidence: 99%
“…Similarly, entrainment of adult fish through the dam during drawdown could have resulted in decreased adult population densities (sensu Stober et al 1983;Post et al 2006), thus resulting in decreased production of offspring. Loss of littoral habitat is deleterious to many fishes, particularly when the loss is a consequence of reservoir drawdown (Paller 1997;Frohnauer et al 2007); low water levels can reduce the availability of adequate spawning habitat (Ploskey 1986;Kallemeyn 1987), which could partially explain the changes we observed in the larval fish assemblage.…”
Section: Larval Fish Assemblagementioning
confidence: 93%